2022
DOI: 10.1101/2022.10.13.512193
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TPL2 kinase activity regulates microglial inflammatory responses and promotes neurodegeneration in tauopathy mice

Abstract: TPL2 (MAP3K8) is a central signaling node in the inflammatory response of peripheral immune cells. We find that TPL2 kinase activity modulates microglial cytokine release and is required for microglia-mediated neuron deathin vitro. In acutein vivoneuroinflammation settings, TPL2 kinase activity regulates microglia activation states and brain cytokine levels. In a tauopathy model of chronic neurodegeneration, loss of TPL2 kinase activity reduces neuroinflammation and rescues synapse loss, brain volume loss, and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…When astrocytes are attacked, however, they release inflammatory mediators and cytokines (iNOS, ROS, etc. ), which are harmful to neurological function [13][14][15]. Previous studies have reported that activated astrocytes from multiple regions in the brain have a negative effect on synapse formation and neuronal function, which may lead to neurodegenerative disorders [16].…”
Section: Introductionmentioning
confidence: 99%
“…When astrocytes are attacked, however, they release inflammatory mediators and cytokines (iNOS, ROS, etc. ), which are harmful to neurological function [13][14][15]. Previous studies have reported that activated astrocytes from multiple regions in the brain have a negative effect on synapse formation and neuronal function, which may lead to neurodegenerative disorders [16].…”
Section: Introductionmentioning
confidence: 99%